Silicon-carbon negative electrode slurry, secondary battery and preparation method of silicon-carbon negative electrode slurry

By adding DMAP to the silicon-carbon negative electrode slurry and reducing binder to inhibit SBR floating, the complete cross-linking of the silicon-carbon negative electrode sheet is achieved, the powder loss and floating problems are solved, and the performance and life of the battery are improved.

CN119495748APending Publication Date: 2025-02-21SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411766919.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials have problems such as spherical anode sheet powder loss and styrene-butadiene rubber (SBR) floating, resulting in poor performance of batteries under high magnification and high energy density conditions.

Method used

By adding 4-dimethylaminopyridine (DMAP) to the silicon carbon negative electrode slurry, the use of binder is reduced, the baking time is improved, and the SBR floatation is inhibited, and the complete cross-linking of the negative electrode sheet is achieved.

Benefits of technology

The goals of rapid production, long life, low cost, high energy density and high magnification of batteries have been achieved, and the problems of powder loss and floating are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495748A_ABST
    Figure CN119495748A_ABST
Patent Text Reader

Abstract

The invention discloses silicon-carbon negative electrode slurry, a secondary battery and a preparation method of the silicon-carbon negative electrode slurry. The invention provides silicon-carbon negative electrode slurry. The silicon-carbon negative electrode slurry comprises 30 to 50 parts of a solid material, 50 to 70 parts of a solvent and 0.05 to 1.2 parts of 4-dimethylaminopyridine, the solid material comprises a silicon carbon material, a conductive material, graphite and a binder; the content of the binder in the solid material is 2 to 3.5 wt%. According to the silicon-carbon negative electrode slurry disclosed by the invention, 4-dimethylaminopyridine is added into the slurry, so that a negative electrode plate can be more thoroughly crosslinked, and the aims of rapid production, long service life, low cost, high energy density and high amplification of a battery are fulfilled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon negative electrode slurry, a secondary battery and a preparation method thereof. Background Art

[0002] The silicon-carbon negative electrode not only has an extremely high gram capacity of 1900mAh -1 (0.8v 50% silicon content), higher lithium insertion potential 0.4V (Li\Li + ) and can also inhibit lithium dendrites. Although the high lithium embedding potential of the negative electrode will cause the overall discharge platform to decrease by about 0.1V; however, due to its extremely high gram capacity, a small amount of doping can increase the gram capacity of traditional negative electrode materials, which has attracted much attention in the new energy industry.

[0003] Based on current technical means, the silicon-carbon anode with excellent performance is achieved by 2 / g of activated carbon is precipitated with silane, and then a carbon shell is precipitated on the surface of the porous carbon through the cracking of alkynes or alkanes. However, because the surface can only be precipitated with alkanes or olefins with relatively low cracking temperatures or their mixed gases; therefore, the surface of the obtained silicon-carbon negative electrode often lacks the support of functional groups, which makes the desolvation of lithium ions more difficult, fast charging is poor, and the necessary hydrogen bonds and van der Waals forces are lacking. The strength and toughness of the carbon shell and the ability to inhibit powder loss or expansion are difficult to meet the requirements of higher energy density batteries. When the battery frequently deinserts and deinserts lithium, it will cause volume expansion. Because the shrinkage rates of the inner and outer layers are different, the silicon-carbon matrix is ​​easily broken, which makes it difficult to meet the current high energy density requirements, especially the requirements of soft-pack batteries based on 3C.

[0004] Although the lithium cobalt oxide system can be controlled at around 70°C during formation through the synergistic effect of some curing agents, binders such as sodium alginate, PAA (polyacrylic acid), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), as well as conductive agents such as carbon nanotubes (CNTs) and acetylene black, the entire negative electrode sheet can be cross-linked at a certain temperature, a certain current density, a certain pressure and a suitable current segmentation interval, thereby inhibiting the shedding caused by repeated expansion, but this often requires a lot of binders, and the binder content used is usually around 4%. Although this method strengthens the electrolyte infiltration of the negative electrode sheet (negative carbon materials often have poor infiltration with the electrolyte), it also affects the migration speed of lithium ions in the main solvent of the electrolyte, which increases the battery impedance. In addition, although temperature can promote the cross-linking speed of PAA (polyacrylic acid), CMC and SBR with silicon nanoparticles, it often does not complete the cross-linking during the formation, and it takes several cycles before it can be done, which will cause water to be produced in the later cross-linking process. Generally, the ideal cross-linking process is completed after the first formation and before the second formation. Incomplete cross-linking during the formation process will lead to continued generation of moisture after the second formation, which will then produce side reactions with the electrolyte.

[0005] In summary, due to the needs of people's lives, lithium-ion batteries are developing in the direction of high rates, and high-rate batteries often require higher lithium ion migration speeds, so it is necessary to make trade-offs from multiple angles such as binder content, packaging type, cell design, and cell formula. Higher-rate batteries often require lower binders. The use of binders can be reduced by using constrained shells, using lower compression designs to enhance wetting and reduce binders, and minimizing the use of silicon-based negative electrode materials in the cell formula to suppress cell expansion and powder loss.

[0006] The existence of the above contradictions requires the design of a new formula system and a comprehensive upgrade of the existing battery system. In view of the current situation where the high amount of silicon and carbon addition is difficult to meet with the current formula, it is particularly important to optimize the formula design. Summary of the invention

[0007] The technical problem to be solved by the present invention is the problems of powder shedding of spherical negative electrode pieces and floating of styrene-butadiene rubber (SBR) in the prior art. The present invention provides a silicon-carbon negative electrode slurry, a secondary battery and a preparation method thereof. By adding 4-dimethylaminopyridine (DMAP) to the slurry, the baking time is increased and the floating of SBR is inhibited while the use of binder is reduced as much as possible; the negative electrode pieces are cross-linked into one, thereby achieving the goals of rapid battery production, long life, low cost, high energy density and high discharge.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] The present invention provides a silicon-carbon negative electrode slurry, which comprises 30-50 parts of solid material, 50-70 parts of solvent and 0.05-1.2 parts of 4-dimethylaminopyridine; the solid material is silicon-carbon material, conductive material, graphite and binder; the content of the binder in the solid material is 2-3.5 wt%.

[0010] It can be understood that the silicon-carbon material can be any silicon-carbon negative electrode material conventionally used in the art.

[0011] In a certain embodiment, the silicon-carbon material is silicon-carbon coated with polyvinyl alcohol. Preferably, in the silicon-carbon coated with polyvinyl alcohol, the mass ratio of silicon-carbon to polyvinyl alcohol is 99:(0.5-1.5); for example: 99:1;

[0012] More preferably, the polyvinyl alcohol-coated silicon carbon is prepared by the following method:

[0013] Phenolic resin, ethanol and urotropine are dispersed, spray dried, cross-linked, carbonized and activated to obtain a porous carbon skeleton;

[0014] The porous carbon skeleton is deposited under a silane mixed gas to form a core body, then deposited under an acetylene mixed gas, and finally deposited under a nitrogen atmosphere to obtain silicon carbon;

[0015] Disperse silicon carbon, polyvinyl alcohol and water and dry them.

[0016] In a certain embodiment, the conductive material is at least one of a carbon conductive material, a metal material and a conductive polymer; the carbon conductive material is at least one of Super P (small particle conductive carbon black), acetylene black, Ketjen black, carbon nanotubes, graphene, carbon fiber or flake graphite; preferably, the carbon conductive material is any two of Super P, acetylene black, Ketjen black, carbon nanotubes, graphene, carbon fiber or flake graphite; for example, acetylene black or carbon nanotubes.

[0017] In one embodiment, the metal material is nano copper particles or nano nickel particles.

[0018] In a certain embodiment, the conductive polymer is polyvinyl alcohol, polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, polybisyne, polyacrylic acid, polyacrylate or polyacrylic acid.

[0019] In a certain embodiment, the number of parts of the solid material is 36-44 parts; for example, 40 parts.

[0020] In a certain embodiment, the number of parts of the solvent is 54-66 parts; for example, 60 parts.

[0021] In one embodiment, the silicon-carbon material has a content of 6-10 wt % in the solid material; for example, 8 wt %.

[0022] In a certain embodiment, the conductive material has a content of 0.8-1.5 wt % in the solid material; for example, 0.88-1.32 wt %; for example, 1.1 wt %.

[0023] In a certain embodiment, the content of the graphite in the solid material is 86-89 wt%; 87.9 wt%, 88.9 wt%, 88.4 wt% or 87.4 wt%; for example 87.9 wt%.

[0024] In a certain embodiment, the content of 4-dimethylaminopyridine in the solid material is 0.1-1.0 part, 0.1 part, 0.3 part, 0.5 part, 0.7 part or 1.0 part; for example, 0.5 part, 0.7 part or 1.0 part; for example, 0.7 part.

[0025] In a certain embodiment, the binder is contained in the solid material in an amount of 2 wt%, 2.5 wt%, 3 wt% or 3.5 wt%; for example, 3 wt%.

[0026] In one embodiment, the solvent is water, for example, deionized water.

[0027] In one embodiment, the mass ratio of the phenolic resin to ethanol is 1:(1-3), for example, 1:2.

[0028] In a certain embodiment, the mass ratio of the phenolic resin to hexamethylenetetramine is 1:(0.04-0.08), for example, 1:0.06.

[0029] In a certain embodiment, the dispersion is carried out by a high-speed dispersing homogenizer; the ball milling speed of the high-speed dispersing homogenizer can be 1000-3000 r / min, for example, 2000 r / min.

[0030] In a certain embodiment, the dispersion time is 50 to 80 minutes, for example 60 minutes.

[0031] In one embodiment, the spray drying temperature is 100-150°C, for example 130°C.

[0032] In one embodiment, the diameter of the particles after spray drying is 6-10 μm; for example, 8 μm.

[0033] In a certain scheme, the crosslinking needs to be carried out by heating, and the heating rate can be 3-5°C / min, for example, 4°C / min; the heating time can be 50min; the temperature is raised to 200°C and kept for 1h.

[0034] In a certain embodiment, the carbonization needs to be carried out by heating, and the heating rate can be 3-5°C / min, for example, 4°C / min; the heating time can be 250-400min.

[0035] In one embodiment, the carbonization temperature is 1200-1800°C.

[0036] In one embodiment, the carbonization must be carried out under inert gas conditions; the inert gas may be nitrogen; the nitrogen supply rate may be 0.8-1.2 L·kg -1 min -1 , for example 1L kg -1 min -1 .

[0037] In one embodiment, the activation is carried out under CO2 conditions; the CO2 supply rate can be 1-3L·kg -1 min -1 , for example 2L·kg -1 min -1 .

[0038] In a certain embodiment, the activation time is 1-10 h, for example 9 h.

[0039] In one embodiment, the activation further comprises a cooling step, wherein the cooling is performed by cooling the furnace temperature to 500-600°C, for example, cooling to 550°C.

[0040] In one embodiment, the silane mixed gas is 20% silane and 80% argon.

[0041] In one embodiment, the ventilation volume of the silane mixed gas is 10-20 L·kg -1 min -1 , for example 15L·kg - 1 min -1 .

[0042] In one embodiment, the temperature of the silane mixed gas deposition is 450-550°C, for example, 500°C.

[0043] In one embodiment, the deposition time of the silane mixed gas is 8-12 hours, for example, 10 hours.

[0044] In one embodiment, the acetylene mixed gas is 20% acetylene and 80% argon.

[0045] In one embodiment, the ventilation volume of the acetylene mixed gas is 4-6 L·kg -1 min -1 , for example 5L·kg -1 min-1 .

[0046] In one embodiment, the acetylene mixed gas deposition temperature is 450-550°C, for example, 500°C.

[0047] In one embodiment, the deposition time of the acetylene mixed gas is 8-12 hours, for example, 10 hours.

[0048] In one embodiment, the temperature of the nitrogen deposition is 20-30°C, for example 25°C.

[0049] In a certain embodiment, the content of acetylene black in the solid material is 0.8-1.2 wt %, for example, 1.0 wt %.

[0050] In one embodiment, the carbon nanotubes are contained in the solid material in an amount of 0.08-0.12 wt %, for example, 0.1 wt %.

[0051] In a certain embodiment, the binder is selected from one or more of sodium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber; preferably sodium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber.

[0052] In a certain embodiment, the content of sodium carboxymethyl cellulose in the solid material is 0.3-0.6 wt %; for example, 0.5 wt %.

[0053] In a certain embodiment, the content of the polyacrylic acid in the solid material is 1.0-2.0 wt %, for example, 1.0 wt %.

[0054] In a certain embodiment, the content of the styrene-butadiene rubber in the solid material is 0.4-1.2 wt %; for example, 0.5 wt % or 1.0 wt %.

[0055] In a certain embodiment, the binder is any of the following embodiments:

[0056] (1) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.0 wt% of polyacrylic acid in the solid material, and 0.5 wt% of styrene-butadiene rubber in the solid material;

[0057] (2) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.0 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material;

[0058] (3) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.5 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material; and

[0059] (4) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 2.0 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material;

[0060] Preferably,

[0061] The solid material contains 0.5 wt% of sodium carboxymethyl cellulose, 1.5 wt% of polyacrylic acid and 1.0 wt% of styrene-butadiene rubber.

[0062] In a certain embodiment, the silicon-carbon negative electrode slurry is any of the following embodiments:

[0063] Scheme 1: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.1 part of 4-dimethylaminopyridine;

[0064] Scheme 2: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.3 parts of 4-dimethylaminopyridine;

[0065] Scheme 3: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.5 parts of 4-dimethylaminopyridine;

[0066] Scheme 4: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of a binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material, and 0.7 parts of 4-dimethylaminopyridine; and

[0067] Scheme 5: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 1.0 part of 4-dimethylaminopyridine;

[0068] More preferably,

[0069] Solution 1: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.5 parts of 4-dimethylaminopyridine;

[0070] Scheme 2: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of a binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material, and 0.7 parts of 4-dimethylaminopyridine; and

[0071] Scheme 3: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material, and 1.0 part of 4-dimethylaminopyridine in the solid material;

[0072] Also preferably,

[0073] The solid material contains 8 wt% of silicon-carbon material, 87.9 wt% of graphite, 3 wt% of a binder, 0.1 wt% of carbon nanotubes, 1 wt% of acetylene black and 0.7 parts of 4-dimethylaminopyridine;

[0074] Wherein, the binder is defined as described in any embodiment of the present invention.

[0075] The present invention provides a method for preparing a silicon-carbon negative electrode slurry, which comprises the following steps of preparing the silicon-carbon negative electrode slurry:

[0076] Dispersing silicon-carbon material, graphite, binder, conductive material, 4-dimethylaminopyridine and water to obtain;

[0077] Wherein, the silicon-carbon material, graphite, binder, conductive material and 4-dimethylaminopyridine are as described in any embodiment of the present invention;

[0078] Preferably, the preparation method further comprises a step of preparing a silicon-carbon material, and the step of preparing the silicon-carbon material comprises: dispersing silicon-carbon, polyvinyl alcohol and water, and drying.

[0079] In one embodiment, in the preparation of silicon-carbon material, the mass ratio of silicon-carbon to water is 99:(4800-5000); for example, 99:4900.

[0080] In a certain scheme, in the preparation of silicon-carbon material, the order of adding materials is first adding silicon-carbon; then adding polyvinyl alcohol and stirring; and finally adding water for dispersion.

[0081] In a certain embodiment, in the preparation of silicon-carbon material, the stirring speed is 300 r / min and the stirring time is 2 h.

[0082] In a certain scheme, in the preparation of silicon-carbon material, the dispersion is carried out by a planetary disperser;

[0083] Preferably, the rotation speed of the planetary disperser is 300 r / min for rotation and 1000 r / min for revolution.

[0084] In a certain embodiment, in the preparation of silicon-carbon material, the dispersion time is 1-3 hours, preferably 2 hours;

[0085] In one embodiment, in the preparation of the silicon-carbon material, the dispersion is performed under vacuum conditions; for example, the vacuum degree is (-0.8) MPa to (-0.1) MPa; for example, -0.9 MPa.

[0086] In a certain embodiment, in the preparation of silicon-carbon material, the drying is spray drying; the temperature of the spray drying can be 120-140°C; for example, 130°C.

[0087] In a certain embodiment, in the preparation of the silicon-carbon material, the particle sizes of the silicon-carbon material are D10=5 μm, D50=8 μm, and D99=20 μm.

[0088] In a certain embodiment, each of the waters is deionized water.

[0089] In a certain embodiment, in the preparation of the silicon-carbon negative electrode slurry, the order of adding materials is: graphite, silicon-carbon material, sodium carboxymethyl cellulose, conductive material, 4-dimethylaminopyridine, water, polyacrylic acid and styrene-butadiene rubber.

[0090] In one embodiment, in the preparation of the silicon-carbon negative electrode slurry, graphite, silicon-carbon material, sodium carboxymethyl cellulose, conductive material and 4-dimethylaminopyridine are added in sequence, and then a planetary disperser is used for the first dispersion; preferably,

[0091] The planetary disperser has a self-rotation speed of 300 r / min and a revolution speed of 1000 r / min.

[0092] The dispersion time is 3h;

[0093] After adding deionized water, a planetary disperser is used for a second dispersion; preferably,

[0094] The second dispersion of the planetary disperser has a rotation speed of 500 r / min and a revolution speed of 600 r / min; the second dispersion time is 1 hour;

[0095] Then, polyacrylic acid is added and dispersed for the third time using a planetary disperser; preferably,

[0096] The third dispersion of the planetary disperser has a rotation speed of 500 r / min and a revolution speed of 500 r / min. The third dispersion time can be 1 hour.

[0097] Finally, styrene-butadiene rubber and water are added and then dispersed for the fourth time using a planetary disperser; preferably,

[0098] The fourth dispersion of the planetary disperser has a rotation speed of 300 r / min and a revolution speed of 300 r / min. The fourth dispersion time may be 1 hour.

[0099] The present invention provides a silicon-carbon negative electrode plate, which is made by using the silicon-carbon negative electrode slurry as described above.

[0100] In a certain embodiment, the method for preparing the silicon-carbon negative electrode sheet comprises the following steps: coating the silicon-carbon negative electrode slurry on a current collector, and baking to prepare a silicon-carbon negative electrode sheet; preferably, the baking temperature is 50°C-130°C; for example, 55°C, 80°C, 110°C or 140°C.

[0101] In a certain embodiment, the baking temperature is 50°C-120°C, for example, 55°C, 80°C or 110°C; for example, 110°C.

[0102] In one embodiment, the current collector is a copper foil; the thickness of the copper foil is 6-10 μm; for example, 8 μm.

[0103] In one embodiment, the coating is double-sided coating.

[0104] In a certain embodiment, during the coating, the coating surface faces the negative electrode of the battery, and the battery may be a button battery.

[0105] In a certain embodiment, during the coating, the thickness of the active material coated on one side is 38-42 μm, for example, 40 μm.

[0106] In a certain embodiment, during the coating, the coating speed is 38-42 cm / s; for example, 40 cm / s.

[0107] In one embodiment, the compacted density of the coating is 1.5-2.0 g / cm 3 ; For example, 1.75g / cm 3 .

[0108] In a certain embodiment, the baking time is 380-420 s; for example, 400 s.

[0109] The present invention also provides the use of the silicon-carbon negative electrode slurry as described above in a battery, wherein the use includes preparing the negative electrode sheet of the battery with the silicon-carbon negative electrode slurry.

[0110] In one embodiment, the battery is a lithium-ion battery.

[0111] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0112] The reagents and raw materials used in the present invention are commercially available.

[0113] The positive progress of the present invention is that the present invention provides a silicon-carbon negative electrode slurry and a secondary battery. By adding DMAP to the slurry, the negative electrode sheet can be more thoroughly cross-linked, achieving the goals of rapid battery production, long life, low cost, high energy density, and high discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0114] Figure 1 It is the measurement position of the compaction density of the pole piece.

[0115] Figure 2 This is the failure cycle diagram of batteries containing different silicon-carbon negative electrode slurries.

[0116] Figure 3 It is the agglomeration phenomenon of active materials in battery electrodes. DETAILED DESCRIPTION

[0117] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0118] Battery preparation method:

[0119] (1) After 1 kg of thermoplastic phenolic resin is fully dissolved in 1 kg of alcohol, 60 g of urotropine is added and spray dried by a spray dryer to prepare a granular dense precursor. The size of the precursor particles can be adjusted by the degree of atomization of the spray dryer. The dried powder is placed in a rotary furnace protected by a nitrogen atmosphere for carbonization treatment. The heating curve is set to 2°C / min, and the temperature is raised to a carbonization temperature between 500°C and 650°C. The temperature is kept for 3 hours. After that, the obtained powder is activated by a CO2 activation method. The air intake is matched with the mass. The activation temperature is 700°C and the activation time is 3 hours.

[0120] (2) Preparation of carbon negative electrode materials: 1 kg of phenolic resin, 2 kg of ethanol, and 60 g of hexamethylenetetramine (HMT) were mixed by a high-speed dispersing homogenizer, and the ball mill speed was 2000 r / min for 60 min. The powder was spray-dried at 130 °C to a particle diameter of 8 μm. The spray-dried powder was placed in a rotary furnace for cross-linking and then carbonization. The heating curve in the front section was 4 °C / min, the temperature was raised for 50 min, and then raised to 200 °C for 1 h. The main purpose was to make the polycarbosilane cross-linked. The heating curve in the back section was 4 °C / min, the temperature was raised for 250-400 min, and the nitrogen atmosphere protection gas supply rate was 1L kg -1 min -1 The porous carbon skeleton was then activated in a CO2 atmosphere for 9 h; the CO2 supply rate was 2 L kg -1 min -1 After cooling to a furnace temperature of 550°C, the atmosphere was switched to a silane mixture (20% silane and 80% argon by mass), and the core was deposited at 500°C for 10 h with a ventilation volume of 15 L kg -1 min -1 Then switch the atmosphere to acetylene mixed gas (20% acetylene and 80% argon by mass percentage) with a ventilation volume of 5 L kg -1 min -1 , continue to deposit at 500℃ for 10h, then switch to nitrogen, and then cool to room temperature 25℃ to obtain silicon carbon.

[0121] (3) Silicon carbon coated with polyvinyl alcohol: Silicon carbon, polyvinyl alcohol and deionized water were dispersed in a mass ratio of 99:1:4900, with a total feed amount of 2 kg. The feeding method was to first add silicon carbon, then add polyvinyl alcohol and stir at 300 r / min for 2 h, then inject deionized water at once, and disperse with a planetary disperser at a rotation speed of 300 r / min and 1000 r / min, with a vacuum degree of -0.09 MPa. After stirring for 2 h, the mixture was spray dried at 130 °C to obtain silicon carbon material. The particle sizes were D10 = 5 μm, D50 = 8 μm and D99 = 20 μm.

[0122] (4) Preparation of silicon-carbon negative electrode slurry: The raw materials are 40 parts of solid material, 60 parts of solvent and 0.1-1 parts of DMAP; wherein the solid material is composed of sodium carboxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber, acetylene black, CNTs, silicon-carbon material and graphite, and the following labeled contents (wt%) are their weight percentages in the solid material; the solvent is water, and the following labeled contents (wt%) are their weight percentages in the solvent; the labeled content (wt%) of DMAP is the weight percentage obtained by comparing it with the sum of the solid material and the solvent.

[0123] The total feed amount is 3kg. The negative electrode formula is designed as CMC (sodium carboxymethyl cellulose): PAA (polyacrylic acid): SBR (styrene-butadiene rubber): SP (acetylene black): CNTs: silicon carbon material: graphite = 0.5 wt%: (1.0-2.0 wt%): (0.5-1 wt%): 1 wt%: 0.1 wt%: 8 wt%: (86.4-88.9 wt%), and DMAP is added to the slurry at 0.1-1 wt%. The specific formula is shown in Table 1. The preparation method of negative electrode slurry is as follows: add graphite, silicon-carbon material, CMC, SP, CNTs and DMAP in sequence, then disperse for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution speed of 1000r / min, inject 80 wt% of deionized water at one time, disperse for 1 hour with a rotation speed of 500r / min and a revolution speed of 600r / min, add PAA and disperse for 1 hour with a rotation speed of 500r / min and a revolution speed of 500r / min, finally add SBR and 20 wt% of deionized water and disperse for 1 hour with a rotation speed of 300r / min and a revolution speed of 300r / min.

[0124] (5) Preparation of negative electrode sheet:

[0125] The silicon-carbon negative electrode slurry is coated on the current collector. The current collector is 8 μm thick copper foil, which is coated on both sides. The coated side faces the negative electrode of the button battery. The thickness of the active material coated on one side is about 40 μm, which depends on the N / P ratio. The compaction density is 1.75 g / cm 3 The coating speed is 40 cm / s, the post-baking temperature is 50°C-130°C, and the drying time is 400s.

[0126] (6) Battery electrolyte formula: The solid content in the formula is: EC (ethylene carbonate) 10 wt%, PC (propylene carbonate) 15 wt%, DEC (diethyl carbonate) 20 wt%, PP (propylene phosphate) 30 wt%, LiPF6 15%, FEC (fluoroethylene carbonate) 7 wt%, PS (phosphate) 2.5%, LiODFB (lithium difluorooxalate borate) 0.5%. The amount of electrolyte added to the button cell is about 0.5 ml. The entire battery is assembled in a glove box to avoid contact with air. The injection coefficient is about 2.0 g / 1000 mAh.

[0127] (7) Positive electrode slurry formula and electrode preparation: The mass ratio of lithium cobalt oxide (LCO): polyvinylidene fluoride (PVDF): acetylene black (SP): carbon nanotubes (CNTs) is 100:1.3:0.6:1. The order and process of adding materials are as follows: LCO, SP, CNTs and polyvinylidene fluoride are added in sequence, and dispersed for 1 hour with a planetary disperser at a rotation speed of 800r / min and a revolution speed of 1000r / min. NMP (N-methylpyrrolidone) is added as a solvent to make the solid content of each component in the positive electrode slurry 72%. The rotation speed is 500r / min and the revolution speed is 500r / min, and the vacuum degree is -0.9, and the dispersion is carried out for 4 hours. The coated current collector uses a 14μm thick aluminum foil, which is coated on one side with the coated side facing the negative electrode of the button battery. The thickness of the coated active material is 40μm and the compaction density is 4.2g / cm3. The coating speed is 40cm / S, the post-baking speed is 85℃, and the drying time is 400s.

[0128] (8) Full cell design: Design N / P=1.1. (N / P=neg capacity per unit area of ​​negative electrode × efficiency of the first three cycles / g capacity per unit area of ​​positive electrode. The full cell is a 100mAh single-chip stacked cell.)

[0129] The obtained materials were tested for gram capacity with button batteries and then assembled into disc batteries, with a designed N / P ratio of 1.1. The disc battery uses a negative-wrapped positive combination of 10 positive electrodes and 11 negative electrodes, with a cell capacity of 1000mAh. The formation process is maintained at 70℃ and a pressure of 10mpa throughout the entire stage, and is divided into three stages. In the first stage, a current of 100ma is used to form to 10% soc, in the second stage, a current of 400ma is used to form to 30% soc, and in the third stage, a current of 700ma is used to form to 90%, and then the battery is charged to 4.4V with 1000mAh.

[0130] Examples 1-20

[0131] Referring to the above preparation method, a negative electrode sheet is prepared according to the negative electrode slurry formula and process conditions listed in Table 1 below, thereby preparing a full battery.

[0132] Table 1 Negative electrode slurry formulations for Examples 1-20

[0133]

[0134]

[0135] Note: The above total adhesive refers to the total amount of CMC, PAA and SBR.

[0136] Comparative Examples 1-6

[0137] Referring to the above preparation method, a negative electrode sheet is prepared according to the negative electrode slurry formula and process listed in Table 2 below, thereby preparing a full battery.

[0138] Table 2 Comparative Example Negative Electrode Slurry Formula

[0139]

[0140] Experimental Example 1

[0141] All the batteries of Examples 1-20 and Comparative Examples 1-6 were discharged, and then fully charged with 1000 mAh for an aging voltage difference test. The cells whose voltage dropped within 50 mv after being fully charged at 45°C for 7 days were selected for testing; all the batteries met the requirements.

[0142] The positive electrode gram capacity is determined by using lithium cobalt oxide as the positive electrode and lithium sheet as the negative electrode with a current of 1mAh, a voltage window of 2.8V-4.4V, and a cut-off current of 0.05mAh.

[0143] Determination of negative electrode gram capacity: The negative electrode sheet is the positive electrode, the lithium sheet is the negative electrode, the current is continuously discharged at 1mAh, the voltage window is 0V-0.8V, and the reversible gram capacity is determined as the gram capacity

[0144] Determination of the first effect: the negative electrode is the positive electrode, the lithium sheet is the negative electrode, and the discharge is continuous at a current of 1mAh. The voltage window is 0V-1.5V. The first effect is obtained by multiplying the coulomb efficiencies of the first three times.

[0145] Compacted density test method: The compacted density measurement method in the embodiment adopts ULTRA1000 true density meter, the particle size measurement adopts Masterizer-2000 laser particle size analyzer, the BET test and full hole test adopt Mack's ASAP2020, and the battery capacity test system adopts Xinwei CT-4008Q-5V6A. Because the cracking of the pole piece is a relatively objective and quantifiable parameter, it is characterized by measuring the ohmic resistance of the pole piece at 0.01MPa. The equipment adopts Yuanneng BER2500. The selected position is 1 minute after the coating starts to enter a stable state. At the 5 equally divided positions on each column of the pole piece, a circle with a unit area of ​​π is selected for testing, such as Figure 1 shown.

[0146] Experimental Example 2 Effect Test

[0147] The batteries of Examples 1-20 and Comparative Examples 1-6 were subjected to a cell failure cycle test according to conventional methods in the art; the experimental instrument was a cell tester: Xinwei, CT-4008Q. During discharge, the battery cycle was discharged at 1000 mA / h to 2.9 V, then discharged at 5 mv / min to 2.8 V, and during charge, it was charged at 1000 mA / h to 4.4 V, then charged at 5 mv / min to 4.45 V before being terminated.

[0148] The battery failure capacity is based on the 800mAh battery capacity, and the number of cycles is the failure cycle parameter.

[0149] Note: -20℃ test needs to keep the room temperature at -20℃ throughout the whole process, 25℃ test needs to keep the room temperature at 25℃ throughout the whole process, 45℃ test needs to keep the room temperature at 45℃ throughout the whole process.

[0150] Failure analysis is shown in Table 3, cell failure cycle number is shown in Table 4, and failure cycle trend is shown in Table Figure 2 .

[0151] Table 3. Failure analysis

[0152]

[0153]

[0154] Among them, the resistivity refers to the resistivity of the unrolled electrode after drying under 1Mpa, which can be used to reflect the cracking situation; the expansion ratio refers to the 50% SOC expansion ratio before and after the failure of the 1C cycle battery at 25 degrees Celsius.

[0155] Table 4. Failure cycles

[0156]

[0157]

[0158] In Table 3, in Comparative Examples 3, 5, and 6, it can be seen that in the same battery slurry formula, as the drying temperature changes, the cycle performance of the battery cell changes. This is mainly because the excessively high temperature makes the pole piece easy to crack after drying, which increases the contact between the active materials and the contact between the current collector and the active material, and is easy to produce powder and active materials falling off in small pieces. This can be seen from the resistivity of the pole piece. The increase in temperature causes the resistivity of the pole piece to rise. This is mainly because the excessively high drying temperature makes it easy for the SBR to float, making the ratio of the living things in the pole piece no longer uniform. In addition, the excessively high drying temperature easily causes the pole piece surface to dry first, while the position of the living things inside the pole piece surface that is not in contact with the air dries more slowly. The thickness of the pole piece after drying is greatly affected by the drying temperature and becomes larger, resulting in insufficient contact distance between the living things and the copper foil, making it easy to fall off.

[0159] In view of the above performance, in the following battery formula DOE experiment process, the comparative example 3 with the most balanced formula was screened out, and the DMAP addition amount was 0-1% and the drying temperature was from 55℃ to 140℃.

[0160] From Example 1 to Example 20, it can be found that the addition of DMAP and the change of drying temperature significantly affect the amount of powder loss and peeling strength when the pole piece is peeled off. The appropriate amount of DMAP added and drying temperature will increase the life of the battery. Under the same slurry formula and the same amount of DMAP added, the increase in drying temperature increases the peeling strength of the battery and then decreases it. This shows that at the appropriate temperature, not only can the drying speed of the pole piece be increased, but the quality of the pole piece can also be improved.

[0161] In addition, it can be seen that the addition of DMAP increases the optimal baking temperature of the electrode from 55°C to 110°C. From the table, it can be seen that the performance of the 110°C battery cell is much better than that of 140°C.

[0162] It can be seen from Examples 3, 7, 11, and 19 that at the optimal baking temperature, the amount of DMAP added is not necessarily the better. When the overall amount of addition is 0.7%, the overall powder loss and peel strength of the electrode can already meet the requirements. Too high an amount of DMAP added can easily lead to residues in the electrode.

[0163] The change in swelling before and after failure in the battery cell is often related to the amount of swelling before and after the initial lithium insertion. Strictly controlling the swelling of the battery cell before and after the first lithium insertion has a great impact on the battery life. Among them, the swelling of the binder after absorption and electrolysis has a great influence on the swelling of the negative electrode material after lithium insertion. Under the premise of unchanged formula and only changing the baking temperature process, the amount of DMAP added affects the swelling of the battery. It can be seen in the examples that a reasonable amount of DMAP added and drying temperature are conducive to reducing the swelling of the battery cell.

[0164] It can also be seen that the different formulations and the amount of DMAP added affect the resistance of the electrode. It can be seen that the resistance in the examples generally reaches the maximum at 110°C, while at 140°C the resistance is large and the battery cell performs poorly.

[0165] from Figure 2 It can be seen that in Comparative Examples 1-4, at (25°C, -20°C), as the binder content increases, the cycle life of the battery cell shows a trend of first increasing and then decreasing. The main reason is that when the binder content is low, the battery pole piece is prone to Figure 3 The agglomeration phenomenon of the active material shown in Figure 3Corresponding to the formula design and process of comparative example 1. This shows that when the content of the binder is low, the active material on the surface of the pole piece is easy to fall off from the surface of the current collector in the form of large chunks. The main reason is that the ratio of CMC and PAA is relatively reasonable, and the insufficient proportion of the binder SBR leads to insufficient toughness of the pole piece as a whole and easy powdering of the active material. With the increase of the content of SBR and PAA, the adhesion of the pole piece is further improved, the amount of powder loss in the peeling test is also reduced, the contact resistance between the particles becomes smaller, and the cycle life is improved. However, with the further increase of the binder content, the migration rate of lithium ions on the surface of the negative electrode decreases, increasing the risk of lithium precipitation, which reduces the cycle life of the battery in comparative example 4. However, this is abnormal at 45°C. It can be seen that with the increase of the binder content, the high temperature cycle stability shows an improving trend. This is mainly because under high temperature conditions, the viscosity of the electrolyte is further reduced, the diffusion of lithium ions becomes faster, the rate of chemical reaction also follows the Arrhenius formula, and the reaction rate constant is exponentially related to temperature, which reduces the concentration difference polarization and electrochemical polarization. Through the three-electrode monitoring system, the potential of the positive and negative electrodes to lithium can be monitored and verified. It can be found that under the same formation process, compared with full charge at room temperature, the potential of the negative electrode to lithium becomes higher, and the potential of the positive electrode to lithium becomes higher, which is a disguised increase in the capacity of the battery. In addition, it can be seen that the cycle performance of the battery cell is the best at 25°C, and the life span will be reduced at too high and too low temperatures. When the temperature is too low, it is easy to produce concentration difference polarization and electrochemical polarization, making it difficult for lithium ions to be concentrated in the negative electrode plate and difficult to embed, resulting in lithium precipitation. When the temperature is too high, although the polarization phenomenon is eliminated, the electrolyte is easy to decompose when the SEI film is formed, which reduces the thickness of the SEI film. For soft-pack batteries, it is easy to produce gas and expand, and eventually the battery cell fails due to electrolyte consumption.

Claims

1. A silicon-carbon negative electrode slurry, characterized in that; It comprises 30-50 parts of solid material, 50-70 parts of solvent and 0.05-1.2 parts of 4-dimethylaminopyridine; the solid material comprises silicon-carbon material, conductive material, graphite and binder; the content of the binder in the solid material is 2-3.5 wt%.

2. The silicon-carbon negative electrode slurry according to claim 1, characterized in that: It meets one or more of the following conditions; (1) The silicon-carbon material is silicon-carbon coated with polyvinyl alcohol. Preferably, in the silicon-carbon coated with polyvinyl alcohol, the mass ratio of silicon-carbon to polyvinyl alcohol is 99:(0.5-1.5); for example: 99:1; More preferably, the polyvinyl alcohol-coated silicon carbon is prepared by the following method: Phenolic resin, ethanol and urotropine are dispersed, spray dried, cross-linked, carbonized and activated to obtain a porous carbon skeleton; The porous carbon skeleton is deposited under a silane mixed gas to form a core body, then deposited under an acetylene mixed gas, and finally deposited under a nitrogen atmosphere to obtain silicon carbon; Disperse silicon carbon, polyvinyl alcohol and water and dry them; (2) The conductive material is at least one of a carbon conductive material, a metal material and a conductive polymer; the carbon conductive material is at least one of Super P, acetylene black, Ketjen black, carbon nanotubes, graphene, carbon fiber or flake graphite; Preferably, The carbon conductive material is any two of Super P, acetylene black, Ketjen black, carbon nanotubes, graphene, carbon fiber or flake graphite; for example, acetylene black and carbon nanotubes; The metal material is nano copper particles or nano nickel particles; The conductive polymer is polyvinyl alcohol, polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, polydiyne, polyacrylic acid, polyacrylate or polyacrylic acid; (3) The solid material is present in an amount of 36-44 parts, for example, 40 parts, and / or the solvent is present in an amount of 54-66 parts, for example, 60 parts; (4) The content of the silicon-carbon material in the solid material is 6-10 wt %; for example, 8 wt %; (5) The content of the conductive material in the solid material is 0.8-1.5 wt %; for example, 0.88-1.32 wt %; for example, 1.1 wt %; (6) The content of the graphite in the solid material is 86-89% by weight; 87.9 wt%, 88.9 wt%, 88.4 wt% or 87.4 wt%; for example, 87.9 wt%; (7) The content of 4-dimethylaminopyridine is 0.1-1.0 part, such as 0.1 part, 0.3 part, 0.5 part, 0.7 part or 1.0 part; preferably 0.5 part-1.0 part; more preferably 0.7 part; (8) The content of the binder in the solid material is 2 wt%, 2.5 wt%, 3 wt% or 3.5 wt%; for example, 3 wt%; (9) The solvent is water, for example, deionized water.

3. The silicon-carbon negative electrode slurry according to claim 2, characterized in that: It meets one or more of the following conditions; (1) The content of acetylene black in the solid material is 0.8-1.2 wt%; for example, 1.0 wt%; (2) The carbon nanotubes are contained in the solid material in an amount of 0.08-0.12 wt %; for example, 0.1 wt %; (3) The binder is selected from one or more of sodium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber; preferably sodium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber; Preferably, The content of sodium carboxymethyl cellulose in the solid material is 0.3-0.6 wt %; for example, 0.5 wt %; The content of the polyacrylic acid in the solid material is 1.0-2.0 wt %; for example, 1.0 wt %; The content of the styrene-butadiene rubber in the solid material is 0.4-1.2 wt %, for example, 0.5 wt % or 1.0 wt %.

4. The silicon-carbon negative electrode slurry according to claim 3, characterized in that: The binder is any of the following: (1) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.0 wt% of polyacrylic acid in the solid material, and 0.5 wt% of styrene-butadiene rubber in the solid material; (2) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.0 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material; (3) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 1.5 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material; (4) 0.5 wt% of sodium carboxymethyl cellulose in the solid material, 2.0 wt% of polyacrylic acid in the solid material, and 1.0 wt% of styrene-butadiene rubber in the solid material; Preferably, The solid material contains 0.5 wt% of sodium carboxymethyl cellulose, 1.5 wt% of polyacrylic acid, and 1.0 wt% of styrene-butadiene rubber.

5. The silicon-carbon negative electrode slurry according to claim 2, characterized in that: The silicon-carbon negative electrode slurry is any of the following: Scheme 1: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.1 parts of 4-dimethylaminopyridine; Scheme 2: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.3 parts of 4-dimethylaminopyridine; Scheme 3: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.5 parts of 4-dimethylaminopyridine; Scheme 4: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.7 parts of 4-dimethylaminopyridine; Scheme 5: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 1.0 part of 4-dimethylaminopyridine; Preferably, any of the following options: Scheme 1: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.5 parts of 4-dimethylaminopyridine; Scheme 2: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 0.7 parts of 4-dimethylaminopyridine; Scheme 3: 8 wt% of silicon-carbon material in the solid material, 87.9 wt% of graphite in the solid material, 3 wt% of binder in the solid material, 0.1 wt% of carbon nanotubes in the solid material, 1 wt% of acetylene black in the solid material and 1.0 part of 4-dimethylaminopyridine; More preferably, The solid material contains 8 wt% of silicon-carbon material, 87.9 wt% of graphite, 3 wt% of a binder, 0.1 wt% of carbon nanotubes, 1 wt% of acetylene black and 0.7 parts of 4-dimethylaminopyridine; Wherein, the binder is defined as described in any one of claims 1-4.

6. A method for preparing a silicon-carbon negative electrode slurry, characterized in that: The method comprises the following steps of preparing a silicon-carbon negative electrode slurry: dispersing a silicon-carbon material, graphite, a binder, a conductive material, 4-dimethylaminopyridine and water to obtain the slurry; wherein the silicon-carbon material, graphite, a binder, a conductive material and 4-dimethylaminopyridine are as described in any one of claims 1 to 5; Preferably, the preparation method further comprises a step of preparing a silicon-carbon material, and the step of preparing the silicon-carbon material comprises: dispersing silicon-carbon, polyvinyl alcohol and water, and drying.

7. The method for preparing the silicon-carbon negative electrode slurry according to claim 6, characterized in that: It meets one or more of the following conditions: (1) In the preparation of the silicon-carbon material, the mass ratio of the silicon-carbon to water is 99:(4800-5000); for example, 99:4900; (2) In the preparation of the silicon-carbon material, the order of adding materials is first adding silicon-carbon; then adding polyvinyl alcohol and stirring; and finally adding water to disperse; (3) In the preparation of the silicon-carbon material, the drying is spray drying; the temperature of the spray drying may be 120-140° C.; for example, 130° C.; (4) In the preparation of the silicon-carbon material, the particle sizes of the silicon-carbon material are D10=5 μm, D50=8 μm, and D99=20 μm; (5) In the preparation of the silicon-carbon negative electrode slurry, the order of adding materials is: graphite, silicon-carbon material, sodium carboxymethyl cellulose, conductive material, 4-dimethylaminopyridine, water, polyacrylic acid and styrene-butadiene rubber.

8. The method for preparing the silicon-carbon negative electrode slurry according to claim 7, characterized in that: It meets one or more of the following conditions: (1) Each of the waters is deionized water; (2) In the preparation of silicon-carbon material, the stirring speed is 300 r / min and the stirring time is 2 h; (3) In the preparation of silicon-carbon materials; the dispersion is carried out using a planetary disperser; preferably, the rotation speed of the planetary disperser is 300 r / min for rotation and 1000 r / min for revolution; (4) In the preparation of silicon-carbon materials, the dispersion time is 1-3 hours, preferably 2 hours; (5) In the preparation of silicon-carbon material, the dispersion is carried out under vacuum conditions; for example, the vacuum degree is (-0.8) MPa - (-0.1) MPa; for example, -0.9 MPa; (6) In the preparation of the silicon-carbon negative electrode slurry, graphite, silicon-carbon material, sodium carboxymethyl cellulose, conductive material and 4-dimethylaminopyridine are added in sequence, and then a planetary disperser is used for the first dispersion; Preferably, the planetary disperser has a dispersion speed of 300 r / min, a revolution speed of 1000 r / min, and a dispersion time of 3 h; After adding deionized water, a planetary disperser is used for a second dispersion; preferably, The second dispersion of the planetary disperser has an autorotation speed of 500 r / min and an orbital speed of 600 r / min; The second dispersion time is 1h; Then, polyacrylic acid is added and dispersed for the third time using a planetary disperser; preferably, The third dispersion of the planetary disperser has a rotation speed of 500 r / min and a revolution speed of 500 r / min; and the third dispersion time is 1 hour; Finally, styrene-butadiene rubber and water are added and then dispersed for the fourth time using a planetary disperser; preferably, The fourth dispersion of the planetary disperser has a rotation speed of 300 r / min and a revolution speed of 300 r / min. The fourth dispersion time is 1 hour.

9. A silicon-carbon negative electrode plate, characterized in that: It is prepared using the silicon-carbon negative electrode slurry as described in any one of claims 6 to 8; Preferably, the method for preparing the silicon-carbon negative electrode sheet comprises the following steps: coating the silicon-carbon negative electrode slurry on a current collector, and baking to prepare a silicon-carbon negative electrode sheet; Also preferably, the baking temperature is 50°C-150°C, for example, 55°C, 80°C, 110°C or 140°C; further preferably, the baking temperature is 50°C-120°C, for example, 55°C, 80°C or 110°C; for example, 110°C; More preferably, the method for preparing the silicon-carbon negative electrode sheet satisfies one or more of the following conditions: (1) The current collector is a copper foil; the thickness of the copper foil is 6-10 μm; for example, 8 μm; (2) The coating is double-sided coating; (3) During the coating, the coating surface faces the negative electrode of the battery, and the battery may be a button battery; (4) During the coating, the thickness of the active material coated on one side is 38-42 μm; for example, 40 μm; (5) During the coating, the coating speed is 38-42 cm / s; for example, 40 cm / s; (6) The compacted density of the coating is 1.5-2.0 g / cm 3 ; For example, 1.75g / cm 3 ; (7) The baking time is 380-420 s; for example, 400 s.

10. A use of the silicon-carbon negative electrode slurry according to any one of claims 6 to 8 in a battery, characterized in that: in, The application includes preparing the negative electrode plate of the battery with the silicon-carbon negative electrode slurry; preferably, the battery is a lithium-ion battery.

Citation Information

Cited By

  • High-compaction-density lithium iron phosphate positive plate and preparation method thereof

    CN122025554A

  • A high-compaction-density lithium iron phosphate positive electrode sheet and a preparation method thereof

    CN122025554B